Evaluation of MAP engineering design parameters on quality of fresh-sliced mushrooms - Oliveira, Felisbela Maria Araújo (2012)
Modified atmosphere packaging (previous termMAPnext term) relies on the interplay between product-respiration and package-film-permeability with the aim of maintaining initial quality and extending shelf-life of fresh produce. This work evaluates the effect of previous termMAPnext term engineering design parameters (amount of product, number of perforations and weight of CO2 scavenger) on quality of sliced mushrooms. Sliced button mushrooms were packed in a tray, covered with cellophane film, and stored at 10 °C for 3 days. Headspace gas composition and chemical and physical quality parameters (weight loss, pH, firmness and colour) were measured throughout the storage period. All design parameters produced a significant effect (p < 0.05) on quality. Addition of CO2 scavenger in the package increased the deterioration of mushrooms. previous termMAP optimisation design requires consideration of mushroom weight and number of film perforations. The optimal conditions found were 110 g of sliced mushrooms and 2 perforations (0.33 mm diameter) which led to an equilibrium gas composition of 3.6% O2 and 11.5% CO2, after 3 days of storage at 10 °C.